Analisis Faktor-Faktor Penyebab Penurunan Kinerja Karyawan Outsourcing Subbagian Pengelolaan Piutang PT. PLN (Persero) UP3 Teluk Naga Tangerang - Yanri Daya Pandera (2021)
This study aims to determine and analyze the cause of the decline in the performance of outsourcing employees in the receivable management sub-section of PT. PLN (Persero) UP3 Teluk Naga. This research uses a qualitative method with a case study approach, data collection techniques in this study were conducted by interview, observation, and documentation methods. Interviews were conducted in a semi-structured manner with five participants, including one supervisor of the accounts receivable management sub-section, two coordinators of the accounts receivable management sub-section, and two representatives of outsourced employees of the accounts receivable management sub-section. To prove the validity of the data in the study, the researcher used the data triangulation method, and then the data was analyzed by performing data reduction, data presentation, and conclusions. The results of the study found three factors, namely Skills & Expertise, Leadership, and Workload which have a mutual attachment to other factors, namely Work Attitude, Motivation, Job Satisfaction, Employee Loyalty, with their respective roles as the cause of the decrease in the quantity of the employee performance outsourcing sub-section management of accounts receivable PT.PLN (Persero) UP3 Teluk Naga Tangerang, which was triggered by the Covid-19 pandemic Condition.